Association of anthropometrics and physical performance measures to golf-specific variables in collegiate male golfers - Donahue, P. T.; Szymanski, D.; Wilson, S. J. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: As physical fitness has become more of a central component of competitive golf it is important to have an understanding of the relationship between anthropometric and physical performance on actual golf performance. Thus, the purpose of this investigation was to determine the relationship between measures of anthropometrics and physical performance to golf swing performance. METHODS: Fourteen division I collegiate golfers performed a battery of tests including the vertical jump, grip strength, rotational medicine ball toss, and sit and reach test in addition to anthropometric measure measurements. Golf specific variables included clubhead speed (CHS), ball velocity (BV) and carry distance (CD) using the participants own driver. Pearson product moment correlations were used to assess the level of relationship between all variables. RESULTS: Statistically significant large positive relationships were found between grip strength and all golf specific variables. Height also showed large significant positive relationship with both CHS and BV. CONCLUSIONS: The association between anthropometrics and physical performance and golf specific variables appear to be limited in a group of collegiate male golfers, outside of grip strength. However, this does not mean that physical fitness is irrelevant to golf performance, but caution should be taken in assuming increase in physical performance will have a direct impact on the golf specific variables.